Study of exchange bias and memory effect in core-shell CoCr2O4 nanoparticles - Jagadish Kumar G.; Rath C. (My University, 2025)
CoCr2O4 of 50 nm particles having core-shell structure demonstrate two different phenomena such as memory effect and exchange bias depending on temperature. The memory effect is responsible for spin glass behavior in the shell and exchange bias is due to core-shell interactions. From magnetization measurement, we observe a long range ferrimagnetic (FiM) order in core and the spin glass behavior at the shell. The spin glass nature is confirmed from memory effect experiment performed using zero field cool (ZFC) protocol below blocking temperature (TB) i.e. 80 K. While the strength of memory effect decreases with decrease in temperature and vanishes at 30 K, the exchange bias increases with decrease in temperature down to 50 K and shows two orders of magnitude more than the bulk at lowest temperature. The high exchange bias field obtained in CoCr2O4 nanoparticles is not only due to the contribution of interface between collinear and non-collinear spin alignment, but also due to spiral ordering below 30 K. While the exchange interaction and strong interface anisotropy results in an exchange bias field (HEB), the training effect have the contribution from the interface as well as from the core shell interaction depending on the particle size. © 2018 Elsevier B.V.